2014
DOI: 10.2478/agp-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

An early Middle Anisian (Middle Triassic) Tubiphytes and cement crusts-dominated reef from North Dobrogea (Romania): facies, depositional environment and diagenesis

Abstract: ABSTRACT:Popa, L., Panaiotu, C.E. and Grădinaru, E. 2014. An early Middle Anisian (Middle Triassic) Tubiphytes and cement crusts-dominated reef from North Dobrogea (Romania): facies, depositional environment and diagenesis. Acta Geologica Polonica, 64 (2), 189-206. Warszawa.A well-developed Triassic carbonate platform is exposed in the eastern part of the Tulcea Unit, in the Cimmerian North Dobrogean Orogen, southeastern Romania. Facies analysis of the 200 m thick succession of lower Middle Anisian limestones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 67 publications
2
30
0
1
Order By: Relevance
“…These species were dwellers of microbial dominated buildups which lack corals or other metazoan frame‐builders and yield only few sponges (Popa et al . ). Thus they may still fall in the category of ‘disaster reef’.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These species were dwellers of microbial dominated buildups which lack corals or other metazoan frame‐builders and yield only few sponges (Popa et al . ). Thus they may still fall in the category of ‘disaster reef’.…”
Section: Discussionmentioning
confidence: 97%
“…Its lithofacies types and depositional environment have been described in detail by Popa et al . (). The early middle Anisian age (i.e.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, Popa et al . () reported Tubiphytes and cement crusts as the main reef builders from the Anisian of North Dobrogea, Romania. The role of microencrusters during the Triassic continued to take more relevance in the Ladinian‐Carnian [Flügel et al .…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, microencrusters were ubiquitous components in reefs, and there are even instances at which they were the main component. For instance, Popa et al (2014) reported Tubiphytes and cement crusts as the main reef builders from the Anisian of North Dobrogea, Romania. The role of microencrusters during the Triassic continued to take more relevance in the Ladinian-Carnian [Flügel et al 2002 (and references therein); Flügel 2010;Sánchez-Beristain & Reitner 2012, 2018Sanchez-Beristain et al 2013;Gale et al 2016Gale et al , 2018], until the Carnian extinction event (Benton et al 2018) and up to the Norian-Rhaetian in the Tehyan realm [e.g.…”
Section: Although Koskinobullina Socialis (Figs 7 8) Canmentioning
confidence: 99%